Penguatan Bahasa Indonesia di Kancah Persaingan Global dan Signifikansinya bagi Studi Filsafat - Yohanes Orong; Taufik Dermawan; Karkono Karkono (Universitas Pendidikan Indonesia, 2022)
The study of Indonesian language issues in higher education states that the low positive attitude of Indonesian citizens towards Indonesian language is the root of the birth of problems surrounding Indonesian language. Therefore, this study affirms the position of Indonesian in the global competition. Through regular and serious efforts to increase vocabulary, the ability of Indonesian vocabulary in expressing intellectual thoughts or in the development of science, technology and art cannot be underestimated. This optimism is supported by the positive attitude of the Indonesian people towards the Indonesian language, the increase of groups who cannot speak Indonesian and groups who are not proficient in Indonesian, the dissemination of codification results (Indonesianization of foreign words and terms) to Indonesian speakers, and the publication of codification results and language development as much as possible. In addition, this study reveals the central position of Indonesian as a means of studying philosophy. This point is intended to further convince the academic community of the philosophy campus of the importance of Indonesian as a means of revealing cultural treasures, a means of logical consideration, and a means of personality development.